I13 Female genital mutilation (fgm) surveillance in under 16 years olds in the uk and ireland. (12th March 2018) - Ayadi O'Donnell, N; Pall, K; Leoni, M; Debelle, G; Lynn, RM; Armitage, A; Creighton, SM; Viner, R; Hodes, D
Abstract : Aims: Female genital mutilation (FGM) is the name given to procedures that involve partial or total removal or other injury to the female genitalia for nonmedical reasons. This study describes the presentation, incidence and clinical management of children with FGM in the UK and Republic of Ireland (ROI). Methods: Cases of FGM were reported using the established national British Paediatric Surveillance Unit (BPSU) reporting system. The data period is from November 2015-November 2017 with a 12 month follow up. Results: These interim results are from 120 cases reported (November 2015-September 2017). 61 (51%) had confirmed FGM, 18 cases were reported in error or were duplicates, 36 questionnaires were incomplete [5 did not meet case definition]. 48% (n=29) of the 61 confirmed cases were classified as type 2. In over 72% of the 61 cases, the parent disclosed child's history of FGM. At the time of diagnosis, 80% of children (n=49) were four years or older (11 cases not recorded). Most children were diagnosed between 5 years and 10 years 11 months (n=27) or 11 years and 15 years 11 months (n=20) with 3 cases diagnosed between 0 and 4 years 11 months. In 51% of cases FGM was said to have been performed when the child was between 0 and 3 years (n=31). 93% (n=57) were performed before arrival to the UK. 13% (n=8) of children had medical symptoms attributed to FGM, with 7% (n=4) of children identified to have mental health symptoms relating to FGM. No children presented with a history of labiaplasty or genital piercing. Conclusion: Numbers reported were lower than expected for UK estimated prevalence with fewer physical and mental health symptoms than anticipated. Further information is needed to determine illegality under UK law. These findings should be used to educate health, social care, police and education on prevention programmes to influence national policies. Funding: Department of Health England.